Systematics of Cyclanthaceae - Leal, Eduardo da Silva (2018)
Cyclanthaceae has ca. 230 species. They are terrestrial herbs, hemiephytic, climbing or epiphytic distributed in the Neotropics, ranging from the South Mexico to Southward Atlantic forest. The family is divided into two subfamilies based on the inflorescence morphology: Cyclanthoideae with staminate and pistillate flowers arranged in alternate whorls, includes only Cyclanthus,; and Carludovicoideae which has a pistillate flower with four surrounding staminate flower, encompass the others genera. Nowadays, phylogenetic studies based on morphological data in generic level were insufficient to clarify its relationship. Furthermore, one of the groups of Carludovicoideae emerged as paraphyletic. In this study we combined morphological and seven molecular markers, five from plastid and two nuclear, in a broad sampling in species level to recover a consistent phylogenetic hypothesis to Cyclanthaceae. We reconstructed a monophyletic Cyclanthaceae with two subfamilies. Genera belonging to Carludovicoideae emerged in three clades: (i) the genus Carludovica, (ii) the Asplundia Clade which includes Asplundia, Dicranopygium and Schultesiophytum; and (iii) the Evodianthus Clade comprising Chorigyne, Dianthoveus, Evodianthus, Ludovia, Sphaeradenia, Stelestylis and Thoracocarpus. All previous known genera were recovered as monophyletic. The Sphaeradenia Group, which includes Chorigyne, Ludovia, Sphaeradenia and Stelestylis, emerged as monophyletic strongly supported by morphological and molecular characters. To maximize the phylogenetic outcome and make the identification easier Dianthoveus is synonymized under Evodianthus. In the Chapter 2 an identification key for all Cyclanthaceae species in Atlantic forest is provided. The endemic species of Asplundia are revisited resulting in three taxa synonymized under A. brachypus, and A. orthostigma newly described. In the Chapter 3 a taxonomic index for all Cyclanthaceae species is provided. We highlighted 225 accepted names and 60 synonyms heterotypics. Four lectotypes and two neotypes are designated. The typification is complemented to four taxa more with second-step lectotypification. Finally, twelve names are placed as synonyms